Antecedent dan Konsekuensi Akuntabilitas Keuangan Desa - Ayudiati, Citra; Endarwati (Journal of Public and Business Accounting, 2020)
Abstract. This study provides an overview of several variables affecting the antecedent level, as well as the consequences of the Village Financial Accountability faktor on other faktors to help understanding the good patterns of the Village Financial Accountability. The subjects of this study were the Village Heads and the members of Rural Technical Staff of Financial Management (PTPKD), consisting of the Village Secretary, Section Head and Treasurer, where the number of PTPKD members determined by a Village Head Decree from 14 villages with each village consisting of 6 correspondents. Therefore, the total correspondents were 84 people. The results showed that the better the level of human resources is, the better the level of accountability of village financial reports is. Beside that, a good understanding of accounting will increase the accountability of village financial reports. The accountability of the Village Financial Report will have a real impact on publik trust and increased publik trust will also have an impact on the level of participation. Furthermore, the use of IT has no influence on the Accountability of Village Financial Statements, and the Accountability of Village Financial Statements does not affect participation. Keywords: Antecedent, Accounting Understanding, Use of TI, Public Trust, Participation, Accountability of Financial Statements